2008
DOI: 10.1161/circresaha.108.173922
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Na/Ca Exchange Results in Increased Cellular Ca 2+ Load Attributable to the Predominance of Forward Mode Block

Abstract: Abstract-Block of Na/Ca exchange (NCX) has potential therapeutic applications, in particular, if a mode-selective block could be achieved, but also carries serious risks for disturbing the normal Ca 2ϩ balance maintained by NCX. We have examined the effects of partial inhibition of NCX by SEA-0400 (1 or 0.3 mol/L) in left ventricular myocytes from healthy pigs or mice and from mice with heart failure (MLP Ϫ/Ϫ handling by refining mode dependence and/or including additional targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 34 publications
8
72
0
Order By: Relevance
“…However, this compensation comes with various consequences, including limiting SR loading and an increased risk of arrhythmias (9). Because of these negative consequences, NCX1 inhibition could be a beneficial therapeutic strategy that has been proposed in ischemiareperfusion, as well as in cardiac hypertrophy and failure (21,23,24,41). However, the regulation of both NCX1 activity and expression is incompletely understood, and the effects of NCX1 targeted therapy especially in light of this study are currently quite unpredictable.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, this compensation comes with various consequences, including limiting SR loading and an increased risk of arrhythmias (9). Because of these negative consequences, NCX1 inhibition could be a beneficial therapeutic strategy that has been proposed in ischemiareperfusion, as well as in cardiac hypertrophy and failure (21,23,24,41). However, the regulation of both NCX1 activity and expression is incompletely understood, and the effects of NCX1 targeted therapy especially in light of this study are currently quite unpredictable.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated that NCX1 inhibitors can act as positive inotropic drugs for the treatment of ischemia-reperfusion injury and congestive heart failure (21,23,41,42). The potential for modulation of NCX1 activity to correct the impaired contractile properties seen in diseased cardiomyocytes makes it an extremely attractive target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such drugs indeed increase SR Ca content, reduce potentially arrhythmogenic currents, but have also unfavorable effects on relaxation [27]. A role for activation of NCX in the setting of heart failure is currently not truly considered and the current paper thus opens an interesting debate.…”
Section: Does An Increase In Ncx Activity Have a Positive Inotropic Amentioning
confidence: 94%